Isolasi Senyawa dan Uji Aktivitas Anti-inflammasi Ekstrak Metanol Daun Puwar Kincung (Nicolaia speciosa Horan) - Penelitian Farmasi Indonesia (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2012)
The study of anti-inflammatory activity and isolation of the methanolic extract, hexane and ethyl acetate fractions of the leaves of puwarkincung (Nicolaia speciosa Horan) have been done. Isolation was carried out by extraction, fractionation and multiple column chromatographicmethod, followed by recrystallization technique. Two compounds were isolated and labeled as F4 and S3. F4 was derived from n-hexanefraction as yellowish-white crystals (20 mg) with mp. 55–57oC and S3 from the ethyl acetate fraction (15 mg) as yellow crystals with mp.68–69oC. Anti-inflammatory activity of methanolic extract using Paw Edema method showed that the dose 250 and 1000mg/kgbw wereactive as anti inflammatory agents.